Implementasi Peraturan Bupati Manggarai Timur Nomor 15 Tahun 2019 tentang Percepatan Penurunan Stunting di Kabupaten Manggarai Timur - Eufronius Gole; Josef Mario Monteiro; Maria Susanti Dalima (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Stunting is a growth and developmental disorder caused by chronic malnutrition that requires integrated policy interventions. To accelerate stunting reduction, the Government of East Manggarai Regency enacted Regent Regulation Number 15 of 2019 concerning the Acceleration of Stunting Reduction. However, the increase in stunting cases in Satar Nawang and Wea Villages in 2025 indicates that the policy has not been implemented optimally. This study aims to analyze the implementation of Regent Regulation Number 15 of 2019 and identify the factors affecting its effectiveness. The research employed an empirical legal method using socio-legal and conceptual approaches. Data were collected through interviews, observations, and literature review, and analyzed qualitatively using the legal effectiveness theory. The findings reveal that the policy has been implemented through supplementary feeding for pregnant women with chronic energy deficiency, exclusive breastfeeding promotion, complementary feeding programs, integrated health post services, and improved access to clean water. The effectiveness of implementation is influenced by human resources, infrastructure, funding, community participation, and the role of community health volunteers. Strengthening institutional coordination, public education, and resource support is therefore essential to improve the effectiveness of stunting reduction programs.